Abnormal intraparotid termination of facial vein and its clinical importance. - Satheesha Nayak B; Srinivasa Rao S; Sapna M; Ashwini LS; Jyothsna P; Ashwini Aithal P; Swamy Ravindra S; Abhinitha P (Department of Surgery, UKM Medical Centre, 2012)
Facial vein is the main vein of the face. Though its origin is constant, it frequently shows variations in its termination. We report a rare type of variation of facial vein. The right facial vein coursed transversely across the masseter, superficial to the parotid duct and entered into the substance of the parotid gland, at its anterior border. Deep dissection of the gland revealed the abnormal termination of facial vein into the superficial temporal vein. The transverse facial vein drained into the facial vein. The superficial temporal vein after receiving the facial vein continued as retromandibular vein. Knowledge of this anomalous course and termination of facial vein may be important for the surgeons doing parotid, maxillofacial and plastic surgeries.